ANALISIS SISTEM AKUNTANSI PERSEDIAAN BARANG DAGANG MENGGUNAKAN METODE FIFO DAN AVERAGE PADA PT DENNIS UTAMA - Wisnu Sukma Maulana (Asosiasi Dosen Muda Indonesia, 2023)
The writer chose PT Dennis Utama as the research object. PT Dennis Utama is a company that distributes food ingredients, namely rice. The researcher obtained primary data from interviews with the sales department of PT Dennis Utama and secondary data from literature studies using analytical techniques, namely flowcharts and descriptive. The analysis used is the FIFO and AVERAGE methods. The aim is to find out the results of the analysis of the inventory accounting information system at PT Dennis Utama using the FIFO and AVERAGE methods. The results of this study are in the form of flowcharts and descriptive results. Based on the results of the study, PT Dennis Utama uses the FIFO and AVERAGE methods which are quite good, there are only a few drawbacks, namely sometimes there is still a little accumulation of goods so that the merchandise becomes damaged and also the company has not implemented a computerized system in its company activities.